Public Sector and Corruption in Nigeria: An Ethical and Institutional Framework of Analysis - Casimir, K. C. Ani; Izueke, E. M.; Nzekwe, I. F. (Scientific Research, 2014)
The paper examines the imperatives of good ethical conduct in the conduct of government business in Nigeria. As government business grows in complexity with the adoption of technological innovations in government, governance in Nigeria’s public sector becomes more problematic and ethically tasking as a result of endemic corruption. An evaluation of the collapse of institutional measures and codes of conduct puts in place to ensure high standard of behavior, using institutional theory suggests that moral contradictions in institutional behavior expectation from the public deepen daily. The perceived lack of an effective ethical organizational framework to coordinate the activities of various institutions has astronomically worsened unethical practices such as corruption in the Nigerian public service. The paper recommends a more realistic African traditional approach to ethical restraint of public servants from indulging in corrupt behavior by subjecting them to customary oath taking based upon the theistic values of fear of sin against mother earth (Ani Casimir, 2009), (a departure from the western style, which sees public service as no man’s business: Ekene, 2012). These core African values that emanate from theistic humanism should also permeate the various anti-corruption organizational frameworks in Nigeria to coordinate the national fight against corruption in the public sector. The behavioral and errant departure of civil servants and Nigeria’s public service from the core human values that ensure transparent private and public conduct of individuals have resulted in underperformance and underdevelopment. It is perceived furthermore that this lack of public service commitment to human values which would have enabled them to consider others above selfish interests, fear divine retribution, dishonor of a good family name, distaste for greed and stealing of public good has weakened the fight against corruption and turned it into a pedantic and cosmetic exercise without results. Therefore, unethical practices and the systemic abandonment of core African human values by the Nigerian public servants oil the wheel of public sector corruption in Nigeria.
Keywords: Public Sector; Ethics; Values; Corruption; Institutional Reforms; Institutions Fighting Corruption in Nigeria-ICPC; EFCC; Code of Conduct Bureau & NAFDAC